Gender differences in shoulder strength, range of motion, and functional movement across a Division III collegiate swim season - Busch, A. M.; Mansfield, T. L.; Barnard, M. L.; Mayio, E. L. (The Sport Journal, 2020)
Background: Musculoskeletal variables used to identify at-risk swimmers for shoulder injuries are inconsistent, possibly resulting from fluctuations in training volume across a competitive season or gender differences in training adaptations.